Review the Potential of Ketogenic Diet and Vitamin B12 Encapsulated Lipid Nanoparticles in Mitochondrial Regulation to Alzheimer's Disease - Reka Febriani; Leunufna, Jaelia; Nur Ananta Aprilia (Talenta Publisher, 2025)
Background: Alzheimer's disease is the most common form of chronic neurodegenerative syndrome characterized by a decline in two to three major cognitive functions, thus significantly reducing the quality of life of sufferers and their families and this disease has no treatment if it has reached a certain stage and even ends in death. Therefore, preventive approaches are the main focus in the development of alternative therapies, one of which is through modifying dietary patterns that are relevant to daily life. Objectives: This literature review aims to analyze the synergistic potential between ketogenic diet and vitamin B12 supplementation encapsulated in lipid nanoparticles in regulating mitochondrial function and inhibiting Alzheimer's disease progression through modulating α-synuclein and amyloid cascade. Methods: The review was conducted with a descriptive approach through an online database search conducted by three authors applying inclusion and exclusion criteria resulting in 69 suitable articles. Result: The analyzed studies showed that both ketogenic diet and vitamin B12 supplementation have significant effects on mitochondrial regulation and protection of neurons from oxidative stress and chronic inflammation. These interventions also contribute to the modulation of α-synuclein and inhibition of amyloid-beta accumulation, both in preclinical and clinical studies. In addition, the application of lipid nanoparticles improves the biocompatibility and avability of vitamin B12 to reach therapeutic targets. Conclusion: the combination of a ketogenic diet and lipid nanoparticle-encapsulated vitamin B12 shows potential as an effective preventive approach to Alzheimer's disease. This study is expected to enrich insights and encourage further clinical research, especially in assessing the long-term effectiveness and potential toxicity of this combination intervention. Keyword: alpha synuclein, Alzheimer's disease, beta amyloid, lipid nanoparticles, vitamin B12 Latar Belakang: Penyakit Alzheimer merupakan bentuk paling umum dari sindrom neurodegeneratif kronis yang ditandai dengan penurunan dua hingga tiga fungsi kognitif utama, sehingga secara signifikan menurunkan kualitas hidup penderita dan keluarganya dan penyakit ini belum memiliki pengobatan jika sudah mencapai stadium tertentu bahkan berakhir pada kematian. Oleh karena itu, pendekatan preventif menjadi fokus utama dalam pengembangan terapi alternatif, salah satunya melalui modifikasi pola diet yang relevan dengan kehidupan sehari-hari. Tujuan: Literatur ini bertujuan untuk menganalisis potensi sinergis antara diet ketogenik dan suplementasi vitamin B12 yang dienkapsulasi dalam nanopartikel lipid dalam meregulasi fungsi mitokondria serta menghambat progresivitas penyakit Alzheimer melalui modulasi α-synuclein dan kaskade amiloid. Methode: Kajian dilakukan dengan pendekatan deskriptif melalui penelusuran pada database online yang dilakukan oleh tiga penulis dengan menerapkan kriteria inklusi dan eksklusi sehingga diperoleh 69 artikel yang sesuai. Hasil: Studi-studi yang dianalisis menunjukkan bahwa baik diet ketogenik maupun suplementasi vitamin B12 memiliki efek signifikan terhadap regulasi mitokondria dan proteksi neuron dari stres oksidatif serta inflamasi kronis. Intervensi ini juga berkontribusi dalam modulasi α synuclein dan penghambatan akumulasi Beta amyloid, baik dalam penelitian preklinis maupun klinis. Selain itu penerapan nanopartikel lipid meningkatkan biokompabilitas dan avabilitas dari vitamin B12 untuk mencapai target terapi. Kesimpulan: Dari hasil kajian ini, kombinasi diet ketogenik dan vitamin B12 enkapsulasi nanopartikel lipid menunjukkan potensi sebagai pendekatan preventif yang efektif terhadap Alzheimer. Kajian ini diharapkan dapat memperkaya wawasan serta mendorong penelitian lanjutan yang lebih mendalam secara klinis, khususnya dalam mengkaji efektivitas jangka panjang dan potensi toksisitas dari kombinasi intervensi ini. Kata kunci: alpha synuclein, beta amyloid, nanoparticle lipid, penyakit Alzheimer, vitamin B12